2016
DOI: 10.23907/2016.004
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Change and its Effect on Evaluation of Fractures

Abstract: Postmortem changes can both mask and mimic trauma, impairing interpretation of the injuries. Bones, while capable of surviving the postmortem period relatively intact, are not immune from these effects. Without attached soft tissue to aid an examiner, it can be difficult to determine the time frame of a fracture's occurrence (i.e., before death, at death, or after death). Bones are composed of both organic and inorganic material, each of which contribute to the biomechanical properties of the bones. With the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…One of the main problems in this field is represented by the immediate post-mortem period, a phase characterized by the persistence of vital reactions (so-called "residual-life phenomena") within a very short time after death [163,164]. In fact, metabolic processes and vital activities do not cease in all the cells and tissues at the same time; so, immediately after death, they could mimic vital reactions, making it hard to differentiate vital from early post-mortem findings [165]. This problem involves a wide range of techniques used in wound vitality evaluation, from immunohistochemistry to miRNAs and proteomics.…”
Section: Timing Of Markers' Positivity Non Specified <1 H <12 H <24 H...mentioning
confidence: 99%
“…One of the main problems in this field is represented by the immediate post-mortem period, a phase characterized by the persistence of vital reactions (so-called "residual-life phenomena") within a very short time after death [163,164]. In fact, metabolic processes and vital activities do not cease in all the cells and tissues at the same time; so, immediately after death, they could mimic vital reactions, making it hard to differentiate vital from early post-mortem findings [165]. This problem involves a wide range of techniques used in wound vitality evaluation, from immunohistochemistry to miRNAs and proteomics.…”
Section: Timing Of Markers' Positivity Non Specified <1 H <12 H <24 H...mentioning
confidence: 99%
“…Differential colouring, the fracture's individual characteristics such as its angle, surface, and contour, the cortex's surrounding flakes, and the inadequate separation of bone fragments from the fracture are all essential in separating the two. The two types of fractures can be hard to distinguish since the changes are not absolute (16).…”
Section: Late Changesmentioning
confidence: 99%
“…Soficaru and Trinkaus' theory is completely incompatible with the morphology and configuration of the Cioclovina fractures. Such postmortem damage on dry, much less fossilized, bone would have produced a very different pattern of fractures from that observed on Cioclovina due to changes in bone biomechanical properties, as extensively stated in the literature on the topic (e.g., _ Işcan & Steyn, 2013); Kemp, 2016;Kristensen et al, 2014;Moritz, 1954) and recently confirmed experimentally (Ribeiro et al, 2020). The configuration presented by Cioclovina (linear fracture and depressed fracture with concentric and radiating fractures) requires the bone to be viscoelastic, and therefore fresh, and is by definition perimortem (Kristensen et al, 2014;Moritz, 1954;_ Işcan & Steyn, 2013).…”
mentioning
confidence: 94%